Atrazine and Nitrate in Public Drinking Water Supplies and Non-Hodgkin Lymphoma in Nebraska, USA. (January 2013) - Rhoades, Martha G.; Meza, Jane L.; Beseler, Cheryl L.; Shea, Patrick J.; Kahle, Andy; Vose, Julie M.; Eskridge, Kent M.; Spalding, Roy F.
A secondary analysis of 1999-2002 Nebraska case-control data was conducted to assess the risk of non-Hodgkin lymphoma (NHL) associated with exposure to nitrate- and atrazine-contaminated drinking water. Water chemistry data were collected and weighted by well contribution and proximity of residence to water supply, followed by logistic regression to determine odds ratios (OR) and 95% confidence intervals (CI). We found no association between NHL risk and exposure to drinking water containing atrazine or nitrate alone. Risk associated with the interaction of nitrate and atrazine in drinking water was elevated (OR, 2.5; CI, 1.0-6.2). Risk of indolent B-cell lymphoma was higher than risk of aggressive B-cell lymphoma (indolent: OR, 3.5; CI, 1.0-11.6 vs. aggressive: OR, 1.9; CI, 0.6-5.58). This increased risk may be due to in vivo formation and subsequent metabolism of N -nitrosoatrazine. A larger study is warranted to confirm our findings.